1991
DOI: 10.1063/1.461432
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution infrared spectroscopy of 2-fluoroethanol in a molecular beam

Abstract: The high resolution infrared spectrum of 2-fluoroethanol (2FE) in a molecular beam was obtained in the region of 2990-2977 cm-1 . This spectral region contains the asymmetric CH stretch of the fluorinated carbon. Excitation of the CH stretch has previously been observed to photochemically isomerize 2FE from the Gg' to the Tt conformation. The high resolution spectrum of this transition provides the information necessary to quantitatively evaluate the amount of vibrational mode-coupling between the asymmetric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 69 publications
(29 reference statements)
1
32
0
Order By: Relevance
“…The experimental apparak,>' has been described in detail elsewhere 22 . Briefly, the molecular beam was created by expanding a mixture of formamide and helium through a 50 gtm n0771e.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental apparak,>' has been described in detail elsewhere 22 . Briefly, the molecular beam was created by expanding a mixture of formamide and helium through a 50 gtm n0771e.…”
Section: Methodsmentioning
confidence: 99%
“…In most previous work, the low frequenc;', large amplitude motion involved torsional motion.s, 6 ,10l,1,1 4 .1s In our previous work on substituted ethanes, we suggested that intramolecular interactions that effect torsional modes, can enhance mode coupling between states involving those torsional modes. 5 ,6, 14 , 15 As noted above, one can view ring puckering in cyclobutane as an extremely hindered torsion, in which the barrier to internal rotation about any C-C bond is essentiai.,. respectively, the K structure is resolved and the weak intensities of these bands prevent us from identifying peak fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental apparatus has been described in detail elsewhere. 5 Briefly, the molecular beam was created by expanding a mixture of cyclobutane and helium through a 50 gm nozzle.…”
Section: Il Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gas phase, excitation of the asymmetric C-H stretch of 2-fluoroethanol [14] does not show conclusive evidence for coupling to other conformers. Evidence for conformation coupling in the gas phase is difficult to obtain since the geometries and thus the rotational constants of the conformers can differ dramatically.…”
Section: Introductionmentioning
confidence: 87%